Language Shift: In Gayo Society - Batubara, Muhammad Hasyimsyah; Shafira, Putri (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
Language is an activity a group of community members uses to work together as a sound symbol system. Language is also a tool for communicating and identifying oneself. Gayo language is the mother tongue in Central Aceh, one of the languages in Indonesia, where this language must be maintained, and its resilience must be preserved. This research was conducted to see the language shift in the Gayo language among the people who live in Takengon. Research method with descriptive qualitative, interview, and observation approaches. The data analysis techniques we use are data collection, presentation, and conclusion. The conclusion obtained is that for now, there should be no worry about the shift in the Gayo language, but many Gayo language users among young people now speak more Indonesian, even though their families are initially from Gayo, so the less use of Gayo language among them. Because of this, it is feared that a shift in language will occur in an alarming direction in the future.